WEB-BASED PRINT ORDER INFORMATION SYSTEM AT DUTA PRINTING AND COPY SIDOARJO - Safira Yuniardani; Nuril Lutfi Azizah; Rohman Dijaya; Arif Senja Fitrani (Journal of Artificial Intelligence and Digital Economy, 2024)
Objective: This study aims to develop a web-based printing ordering information system to improve the efficiency and service quality of Duta Printing & Copy, a business that previously relied on manual order recording methods. Method: The research applies a system development approach using PHP as the programming language and a MySQL database to manage order, payment, and customer data. The system design follows the waterfall model, including analysis, design, implementation, and testing stages to ensure reliability and usability. Results: The developed web-based system successfully accelerates the ordering process, minimizes human error, and provides real-time access to payment and order status information. This improvement enhances operational efficiency and customer satisfaction. Novelty: The study presents an integrated digital solution tailored for small-scale printing businesses, bridging the gap between traditional manual services and digital automation, thereby offering a practical model for digital transformation in local service enterprises.